2018
DOI: 10.1515/pac-2017-0910
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation kinetics of irreversible patches coupled with reversible isotropic interaction leading to chains, bundles and globules

Abstract: In the present study we are performing simulation of simple model of two patch colloidal particles undergoing irreversible diffusion limited cluster aggregation using patchy Brownian cluster dynamics. In addition to the irreversible aggregation of patches, the spheres are coupled with isotropic reversible aggregation through the Kern-Frenkel potential. Due to the presence of anisotropic and isotropic potential we have also defined 3 different kinds of clusters formed due to anisotropic potential and isotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 63 publications
(80 reference statements)
1
15
0
Order By: Relevance
“…We observe that <Z NPI > value for ω ≤ 22.5 • after a plateau takes a sudden upturn at t/t 0 ≥ 100. This upturn is similar to nucleation and growth mechanism 42 and it indicates chain to bundle transition 38 . The snapshot of system formed at ω = 22.5 • is shown in Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…We observe that <Z NPI > value for ω ≤ 22.5 • after a plateau takes a sudden upturn at t/t 0 ≥ 100. This upturn is similar to nucleation and growth mechanism 42 and it indicates chain to bundle transition 38 . The snapshot of system formed at ω = 22.5 • is shown in Fig.…”
Section: Resultssupporting
confidence: 70%
“…Patchy particles are also considered to be building blocks of various supracolloidal helices [35][36][37] . Two patch model along with isotropic interaction reproduced the chain to bundle transition usually seen in Lysozyme protein 38,39 . They also showed the coexistence of thermodynamically favored bundles along with equilibrium crystals 40 .…”
Section: Introductionmentioning
confidence: 85%
“…Bundle formation is also observed in other biological systems like the actin filaments [19]. Chain to bundle transition was shown for a two patch particle where irreversible patchy interaction was coupled with reversible isotropic interaction [20]. Huisman et al [21] also observed the formation of bundles and they showed that transition is similar to sublimation transition of polymers.…”
mentioning
confidence: 89%
“…u a is non zero only ifr i,j .v i > cos ωandr j,i .v j > cos ω, where ω is the semi solid angle of a cone having vertex at the center of a sphere which defines the patch size. In the present work we have used σ = 1, = 0.1 and ω = π/8 which ensures that only one bond per patch is possible [20]. In the present study, all quantities are reported in reduced units, hence bond strength is measured in units of u/k B T where k B T = 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation